PENGARUH KEPEMIMPINAN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi pada karyawan bagian produksi lemari pendingin PT.Hartono Istana Teknologi Sayung-Demak) - Burhanuddin, Muhammad Fuad; Widodo, Untung (STIE PENA, 2022)
This study aims to determine the effect of leadership, motivation and work environment on employee performance at PT. Hartono, Sayung-Demak Technology Palace. PT Hartono palace technology continues to improve employee performance, because large companies want production to run well, on time and with quality. The tendency that occurs when employees work without support from company leaders, such as giving bonuses, employee motivation and the work environment can result in decreased employee performance. The data shows that there has been a fluctuation in the target and realization of the production of refrigerators at PT Hartono Istana Teknologi for the period March 2016 to February 2020 from the average target of 42628 units but down to an average production realization of 34182 units, meaning that employee performance is not good, therefore this study takes three independent variables and one dependent variable, namely employee performance. The population in this study were employees of the refrigerator production division at PT. Hartono, the Sayung-Demak technology palace, totaling 90 respondents. The sampling technique used in this study is the census method, where all populations are used as samples. Data analysis uses validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, t test, F test, and coefficient of determination test (R2). The results showed that the F test results were 39.358 with a significance value of 0.000. The t-test shows that leadership, motivation and work environment have a positive and significant effect on performance. The result of the coefficient of determination (R2) shows that some variations in performance can be explained in the variables of leadership, motivation and work environment by 56.4%. The results show that leadership, motivation and work environment have a positive and significant effect on employee performanceKeywords: leadership, motivation, work environment and employee performance.